Amaranthus bengalense (Amaranthaceae) a new species from India, with taxonomical notes on A. blitum aggregate - Das, Saubhik; Iamonico, Duilio (Phytotaxa, 2014)
Amaranthus bengalense from lower Gangetic plain of West Bengal (India) is proposed and described as new species for science. It belongs to Amaranthus subgen. Albersia, and is part of the A. blitum aggregate (also including A. blitum s.l., and A. emarginatus s.l.). A morphometric analysis of specimens collected in Europe and India is performed. The new species is clearly distinct from the others being characterized by the following combination of characters: leaves with apex obtuse or slightly emarginate, bracts long as well as the tepals (ratio bract/tepal about 1), tepals acuminate, seed with diameter 0.7–1.0 mm. Finally, a key of the taxa belonging to the Amaranthus blitum aggregate is provided.